PERANAN BANTUAN KONSELING PSIKOLOGIS DALAM KEPOLISIAN - Tugimin Supriyadi; Anisa Ramadani, Ade Saputra, M. Fathul Kamal (ADISAM PUBLISHER, 2026)
In the National Police institution, police psychologists are distinctive in relation to counseling guidance to problematic members in the service, so there are several professional competencies required for the psychology profession in the police environment. With counseling services, it is expected that there will be handling to improve professionalism in members of the Police. The type of research design used in this study is a type of literature review research where journal references are collected using the Google Scholar database. Based on the results of the literature review found, it was found that there was still quite a lack of psychological counseling for police personnel However, it has also been found that there are several types of counseling services that can be provided to police personnel.